Implementation of Online Learning: Case Study of Anti-Drug Counseling Course - Hafifatul Auliya Rahmy (UIN Sulthan Thaha Saifuddin Jambi, Pusat Kajian Kurikulum Pengembangan Pengajaran dan Pembelajaran (Center of Curriculum Studies, Teaching and Learning Development), 2022)
The COVID-19 pandemic impacts university learning, typically involving face-to-face instruction. This study investigated the implementation of online learning during the COVID-19 pandemic in anti-drug counseling courses and the factors that hindered and supported it. This type of research is descriptive and quantitative, with a sample of 67 students taking anti-drug counseling courses and using a questionnaire distributed online via Microsoft Form to collect the data. The data analysis used is a descriptive analysis by presenting the frequency distribution. The results showed that 75% of students agreed that online learning increased learning independence, 75% were interested in learning with learning media (video, PowerPoint presentation), 45% said students learning was well organized, and 48% stated lecturer-student interactions well. The provided learning model combines the use of the Google Classroom, Zoom meeting, and WhatsApp applications. The inhibiting factor in online learning is the internet signal that not all students can access adequately. Because many students are in areas where the possibility of internet signals is still limited, this existing obstacle causes students not to be able to follow the learning provided by the lecturer online fully. Factors supporting online learning are that the university facilitates wifi for lecturers and combines learning media synchronous and asynchronous.